Prospective registry of non-ST-elevation acute coronary syndrome in a regional vascular center (CONTRAST). Study design and outcomes of the hospital stage - S. Yu. Martsevich; E. P. Kalaydzhyan; A. V. Zagrebelny; A. N. Borodin; N. P. Kutishenko; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To evaluate the real-world practice of diagnosing non-ST-elevation myocardial infarction (NSTEMI) and unstable angina (UA) in patients admitted with a diagnosis of non-ST-elevation acute coronary syndrome (NSTE-ACS) to a regional vascular center of one of the Moscow region cities.Material and methods. The prospective registry of NSTE-ACS in a regional vascular center (CONTRAST) included all patients consistently admitted with a diagnosis of NSTE-ACS from October 2018 to March 2019. Upon admission, all patients underwent coronary angiography (CAG). Percutaneous coronary intervention (PCI) was considered depending on the CAG data, as well as the clinical condition of the patients, electrocardiographic and medical history data. At the time of CAG and the decision for PCI, the blood troponin levels were unknown.Results. The study included 136 patients, of whom 83 (61%) were men. The mean age of patients was 63,8±10,9 years, ranging from 38 to 93 years. At hospital discharge, UA was diagnosed in 112 (82,4%) patients and NSTEMI — in 24 (17,6%). UA was more common in female patients than NSTEMI — 40,2 vs 33% (p>0,05). NSTEMI, on the contrary, was more common in males — 66,7 vs 59,8% (p>0,05). Patients with NSTEMI were older than patients with UA — 69 years vs 63 years (p=0,011). Patients with NSTEMI were significantly more likely to have a prior MI — 58 vs 32% (p=0,029). According to angiographic data, patients with NSTEMI demonstrated a higher prevalence of multivessel coronary artery disease — 50 vs 26,8% (p=0,041). Predominantly in patients with NSTEMI, an increase in the troponin I level was observed — 83 vs 50% (p=0,011). In patients with UA, emergency PCI was performed significantly less frequently compared to patients with NSTEMI — 28 vs 67% (p=0,001). When prescribing dual antiplatelet therapy in a hospital, ticagrelor was preferred as the second drug in patients with NSTEMI — 50 vs 10% (p<0,001), while in patients with UA, on the contrary, clopidogrel was used more often — 84 vs 50% (p<0,001).Conclusion. The results suggest that when making a definitive diagnosis, doctors were more focused on the medical history, the clinical condition of patients, ECG and echocardiography abnormalities, and the severity of CAG changes. Data on cardiac specific troponin levels were less often considered.